Analysis of Loyalty and Fanatism Factors in the Psyhco Sociologys of Psim Jogja Supporters Throughout the Anthem Aku Yakin dengan Kamu - Wibiyanto, Agung; Syaifullah, Jahid; Dani, Jeratallah Aram; Sudarmaji, Sudarmaji (Universitas Syiah Kuala, 2025)
In writing this article will review the analysis of loyalty and fanaticism factors in the Psycho Sociology of PSIM Jogja supporters tucked away in the Anthem